2022
DOI: 10.3390/jcm12010081
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Diet in Older Women: A Narrative Review

Abstract: Physical activity and diet are essential for maintaining good health and preventing the development of non-communicable diseases, especially in the older adults. One aspect that is often over-looked is the different response between men and women to exercise and nutrients. The body’s response to exercise and to different nutrients as well as the choice of foods is different in the two sexes and is strongly influenced by the different hormonal ages in women. The present narrative review analyzes the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 92 publications
0
11
0
Order By: Relevance
“…However, it was related to age, sex, cognition, depression, frailty, mobility and physical activity level. Many factors are thought to contribute to the higher prevalence of frailty in women than in men, including biological and genetic factors, social roles, dietary choices, attitudes toward health, and physical activity habits [ 42 , 43 ]. A previous study revealed vitamin D deficiency was significantly associated with sarcopenia only in men, low physical activity was significantly associated with higher odds of sarcopenia in women only, and low physical activity was significantly associated with obesity, sarcopenia, and sarcopenic obesity only in participants with vitamin D deficiency [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it was related to age, sex, cognition, depression, frailty, mobility and physical activity level. Many factors are thought to contribute to the higher prevalence of frailty in women than in men, including biological and genetic factors, social roles, dietary choices, attitudes toward health, and physical activity habits [ 42 , 43 ]. A previous study revealed vitamin D deficiency was significantly associated with sarcopenia only in men, low physical activity was significantly associated with higher odds of sarcopenia in women only, and low physical activity was significantly associated with obesity, sarcopenia, and sarcopenic obesity only in participants with vitamin D deficiency [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the increasingly high CAD in women, low CR and physical activity in women are becoming an increasingly important problem [53,54]. Experts offer various opinions about women's low CR referral, enrollment, and completion rates.…”
Section: Discussionmentioning
confidence: 99%
“…We have reported this gap in older women; however, it could also be translated in younger women. 4 An interesting result of the manuscript by AlQuaiz et al is that the majority (87%) of participants reported drinking Arabic coffee frequently, and most of them drank three to five cups per sitting. A dose–response association was observed between the symptoms and increasing number of cups of coffee consumed.…”
Section: Dear Editormentioning
confidence: 97%